2006
DOI: 10.1002/dvdy.20795
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids and spermatogenesis: Lessons from mutant mice lacking the plasma retinol binding protein

Abstract: Using Rbp4-null mice as models, we have established for the first time the kinetics of the spermatogenetic alterations during vitamin A deficiency (VAD). Our data demonstrate that the VAD-induced testicular degeneration arises through the normal maturation of germ cells in a context of spermatogonia differentiation arrest. They indicate that retinoic acid (RA) appears dispensable for the transition of premeiotic to meiotic spermatocytes, meiosis, and spermiogenesis. They confirm that RA plays critical roles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 75 publications
(136 reference statements)
5
71
0
Order By: Relevance
“…2 H and K). It must be stressed that spermatogenesis can resume in Rbp4-null males if vitamin A is restored in the diet or if RA is administered (24). These results indicate that RA-activated RARA in SC is able to drive the initial transition from Aal to A1 spermatogonia, but not the following ones and suggest that RA needs to act elsewhere in the seminiferous epithelium to induce subsequent cycles of spermatogenesis.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…2 H and K). It must be stressed that spermatogenesis can resume in Rbp4-null males if vitamin A is restored in the diet or if RA is administered (24). These results indicate that RA-activated RARA in SC is able to drive the initial transition from Aal to A1 spermatogonia, but not the following ones and suggest that RA needs to act elsewhere in the seminiferous epithelium to induce subsequent cycles of spermatogenesis.…”
Section: Resultsmentioning
confidence: 91%
“…According to our study, it is now conceivable that the signal committing gonocytes to differentiation as A1 spermatogonia relies on RA-activated RARA in SC. However, undifferentiated spermatogonia also rely on RA as attested by the requirement of retinol (or RA) to resume spermatogenesis in VAD adult males (3,24). The Aal-to-A1 transitions during all but the first wave of spermatogenesis may depend on RAR-dependent signals distinct from those controlled by RARA in SC for commitment of gonocytes.…”
Section: Resultsmentioning
confidence: 99%
“…7,8 RA functions inside the nucleus recognising two different classes of retinoid receptors. Both classes (RARs and RXRs) consist of three types of receptors, α, β and γ, encoded by distinct genes 9 and transduce RA signal by binding directly to retinoic acid responsive elements (RARE). During post-natal development, each RAR is detected predominantly in a specific cell type of the seminiferous epithelium: RAR α in Sertoli cells, RAR β in round spermatids and RAR γ in A spermatogonia.…”
Section: Introductionmentioning
confidence: 99%
“…An opportunity to explore this question experimentally arises from recent studies of Stra8 (Stimulated by retinoic acid gene 8), a vertebrate-specific gene that encodes a cytoplasmic protein and whose expression is induced by retinoic acid (6)(7)(8)(9)(10)(11). Our laboratory previously reported that, in female mice, Stra8 is expressed in embryonic ovarian germ cells shortly before they enter meiotic prophase (12).…”
mentioning
confidence: 99%